Coronary sinus filling time as a marker of microvascular dysfunction in patients with angina and normal coronaries - Farshad Shakerian; Nasrin Panahifar (Research in Cardiovascular Medicine, 2019)
Objective: Although chest pain and normal coronary arteries (known as cardiac syndrome X [CSX]) remained a prevalent clinical condition, underlying pathogenesis has not been fully explained. Microvascular dysfunction has been considered as the most likely cause of CSX. In this research, we attempted to evaluate the coronary sinus filling time (CSFT) at angiographic films, and also introducing it as a new indicator for microvascular function. Patients and Methodology: Patients with typical angina or abnormal chest pain with stress-induced ischemia in prior stress tests formed angina group and control group consisted of patients with severe mitral stenosis underwent coronary artery angiography before the balloon mitral valvuloplasty. CSFT was explained as the time necessary for the contrast with pass through myocardial capillaries and reach to the coronary sinus origin at coronary angiography. Furthermore, thrombolysis in myocardial infarction (TIMI), frame count, and myocardial blush score were evaluated for each group. At the end, we compared these parameters and reported the results. Results: The angina group consisted of 128 patients and there were 71 patients in the control group. The mean of the CSFT in angina group was 47.2 ± 9.9 (in frame count), which was greater than the mean of the control group (mean: 32.2 ± 3, P = 0.0001). Corrected TIMI frame count was 21.1 ± 3.4 in angina group and 20.1 ± 3.1 in the control group, and the differences were not statistically significant (P = 0.75). Myocardial blush score in the angina and the control group had not indicate any meaningful difference (P = 0.52). Conclusion: CSFT in contrast with TIMI frame count and myocardial blush score, was significantly prolonged in patients with angina and normal coronary arteries.